ДОСЛІДЖЕННЯ УКРАЇНСЬКИХ НАРОДНИХ ПІСЕНЬ У КОНТЕКСТІ ГЕНДЕРОЛОГІЇ - Помирча, Світлана; Клименко, Олександра (Збірник наукових праць Уманського державного педагогічного університету, 2020)
У статті аналізуються тексти українських народних пісень у контексті гендерної лінгвістики, що дає змогу не тільки відобразити дійсність українського народу в минулому, а й дослідити функціонування гендерних стереотипів на сьогоденні. У роботі предметом уваги слугували мовні одиниці, які вербалізують образ жінки в народних піснях. В роботі застосовано методи аналізу й синтезу – для узагальнення наукових теорій і концепцій, класифікаційний – для класифікації гендерних стереотипів і мовних одиниць, які їх вербалізують. В статье анализируются тексты украинских народных песен в контексте гендерной лингвистики, что предоставляет возможность не только отобразить действительность украинского народа в прошлом, а и исследовать функционирования гендерных стереотипов на сегодня. В работе внимание уделялось языковым единицам, которые отображают образ женщины в народных песнях. В работе использовался метод анализа и синтеза – для обобщения научных теорий и концепций, классификационный – для классификации гендерных стереотипов и языковых единиц, которые их изображают. Language analysis shows that the folk songs, the gender stereotypes are manifested at all levels of language. The investigation of Ukrainian folk and contemporary songs is relevant in the context of gender theory, because it allows not only to reflect the reality of the Ukrainian people in the past, but also examine the functioning of gender stereotypes at that time, and match them with a range of those available in the Ukrainian society nowadays. This article analyzes the texts of Ukrainian folk songs in the context of gender linguistics, because it allows not only to reflect the reality of the Ukrainian people in the past, but also examine the functioning of gender stereotypes in the present. The linguistic units that verbalize the image of women in folk songs are the object of attention. The paper used the methods of analysis and synthesis to summarize the scientific theories and concepts, classification for the classification of gender stereotypes and language units.